2008
DOI: 10.1021/jo802061p
|View full text |Cite
|
Sign up to set email alerts
|

To Flip or Not To Flip? Assessing the Inversion Barrier of the Tetraphenylene Framework with Enantiopure 2,15-Dideuteriotetraphenylene and 2,7-Dimethyltetraphenylene

Abstract: Two chiral tetraphenylenes, 2,15-dideuteriotetraphenylene (7) and 2,7-dimethyltetraphenylene (15) were synthesized and resolved to address the tetraphenylene inversion barrier problem. Neutron diffraction investigation of enantiopure 7 showed that the molecule retained its chirality integrity during its synthesis from enantiopure precursors and therefore rules out the possibility of the tetraphenylene framework possessing a low-energy barrier to inversion. Thermal study on 15 and tetraphenylene 1 further revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…Later, Eisch examined various nickel complexes for this reaction, and found that the ligands attached to the metal center of nickel complexes played a crucial role in the oxidative insertion into the strained C-C bond of 5 [15]. For example, complex Ni(COD) 2 was unreactive towards 5, whereas Ni(Et 3 P) 4 completely even at 0 • C. Importantly, a dibenzonickelole intermediate (9) was proposed to be involved in the reaction mechanism (Scheme 5). Then, 9 lost Et 3 P and dimerized to a dinuclear nickel complex (10) (R = Et), whose structure was determined by an X-ray diffraction study.…”
Section: Pyrolysis And/or Metal-catalyzed Dimerization Of Biphenylenesmentioning
confidence: 99%
See 3 more Smart Citations
“…Later, Eisch examined various nickel complexes for this reaction, and found that the ligands attached to the metal center of nickel complexes played a crucial role in the oxidative insertion into the strained C-C bond of 5 [15]. For example, complex Ni(COD) 2 was unreactive towards 5, whereas Ni(Et 3 P) 4 completely even at 0 • C. Importantly, a dibenzonickelole intermediate (9) was proposed to be involved in the reaction mechanism (Scheme 5). Then, 9 lost Et 3 P and dimerized to a dinuclear nickel complex (10) (R = Et), whose structure was determined by an X-ray diffraction study.…”
Section: Pyrolysis And/or Metal-catalyzed Dimerization Of Biphenylenesmentioning
confidence: 99%
“…However, it is unfortunate that mononuclear 9 could not be isolated for structural characterization. The likely existence of 9 was nonetheless proved by its reactivity with deuterium hydrochloride (DCl), LiAlH 4 , and CO, leading to the respective desired products. Notably, the structures of 9 and 10 lend support to a unified mechanistic scheme for interpreting the nickel-catalyzed Reppe tetramerization reaction of acetylenes to COT [16].…”
Section: Pyrolysis And/or Metal-catalyzed Dimerization Of Biphenylenesmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, Wong and co-workers have comprehensively studied the asymmetric synthesis and the use of chiral poly(hydroxy)tetraphenylenes. [8] The only example of an enantioselective synthesis is the sparteine-mediated lithiation of 2,2'-dibromobiphenyl derivatives and subsequent coupling using an excess amount of CuBr 2 , for which moderate enantioselectivity was achieved. [9] Herein we disclose a new [2+2+2] cycloaddition-based strategy for the synthesis of substituted tetraphenylenes, and its application to asymmetric synthesis.…”
mentioning
confidence: 99%